Sodium-Glucose Co-Transporter 2 Inhibitors for Non-Alcoholic Fatty Liver Disease in Asian Patients With Type 2 Diabetes: A Meta-Analysis - Wong, Chloe; Yaow, Clyve Yu Leon; Ng, Cheng Han; Chin, Yip Han; Low, Yi Fen; Lim, Amanda Yuan Ling; Muthiah, Mark Dhinesh; Khoo, Chin Meng (Frontiers in Endocrinology, 2021)
Objective: Non-alcoholic fatty liver disease (NAFLD) is a very common disorder among patients with type 2 diabetes and may share causal relationship. Type 2 Diabetes is a risk factor for the risk of progression and poor outcomes in NAFLD patients. This meta-analysis aimed to analyze the current evidence of sodium-glucose co-transporter-2 inhibitors (SGLT2i), a glucose-lowering drug to improve NAFLD in patients with Type 2 Diabetes. Methods: Medline, Embase and Cochrane Central Register of Controlled Trials were searched for articles examining efficacy of SGLT2i on treatments of NAFLD in type 2 diabetes in July 2020, and articles were sieved. Continuous data were extracted in the form of mean and standard deviation, and were pooled with standardized mean difference (SMD). Results: 10 articles involving 555 patients from 7 randomized controlled trials (RCTs) and 3 cohort studies, were included in this meta-analysis. Our analysis revealed significant improvements in hepatic fat content, AST, ALT, body composition, glycemic control, lipid parameters, inflammatory markers and insulin sensitivity after SGLT2i treatment, and when compared against controls. There was a trend in the improvement in fibrosis markers after SGLT2i treatment. Conclusions: SGLT2i is an effective treatment to improve NAFLD among patients with type 2 diabetes. Further studies are needed to understand the direct and indirect effects of SGLT2i on NAFLD and if SGLT2i could prevent the progression of NAFLD or NASH. We recommend that patients with type 2 diabetes and NAFLD should be given SGLT2i, if there are no contraindications.